"Colecionar é voltar no tempo": Histórias e memórias da gestão de colecionadores mineiros - Gabriel Farias Alves Correia (2023)
of this thesis was to comprehend how certain private collections in Minas Gerais are formed and managed, over time and space, by the participants of this study. We started with the assertion that tracking personal collecting characterizes itself as a subject within Administration, given that the collected objects pose management challenges in both temporal and spatial dimensions. In this pursuit, we reflected on stories and memories with Walter Benjamin, presenting the theoretical and philosophical foundations that guided us through our process. The paths and crossroads unfolded through a qualitative-historical work involving 29 collectors of various items and five collecting groups from Minas Gerais, encompassing their oral narratives. We triangulated this data with document analyses, photographs in conjunction with field notebook notes. The data were interpreted based on the guiding assumptions of Narrative Analysis, allowing us to reflect on categories linked to theoretical reference points from a historical organizational perspective. Building upon these guiding assumptions, we relied on a combination of data-based coding process, reference points, and a flexible field approach to attain the subcoding of collecting memories. Out of this emerged six narratives that composed the analyses on the objects and aspects of collecting: being a collector, encompassing perspectives on the initiation of the practice; the focus of collecting practice, highlighting the past within narratives; collector groups and the interweaving of individual and collective memory; management aspects, spotlighting the present time and spanning from object acquisition, storage, spaces, object maintenance to economic matters; finally, we analyzed data pertaining to the various possible futures of collections, highlighting potential future scenarios. The data suggests an interconnection of past, present, and future processes as a phenomenon that must be examined as a continuum.In conclusion, we wrap up our work by reflecting on the necessity of an Administration that takes into consideration the dimensions of time, space, and emotions in favor of rejecting boundless productivity. Considering collecting aspects, recollection, nostalgia, and contemplation, we encourage a multitude of ways of being, existing, and managing characteristic of the global South, which, in its discontinuities and ruptures, presents modes of breaking through the gaps and fissures of a traditional, functionalist, and productivity-oriented administration.